Data from: Modelling vaccination strategies against Rift Valley fever in livestock in Kenya: model code - Gachohi, John M.; Njenga, M. Kariuki; Kitala, Phillip M.; Bett, Bernard K.; Bett, Bernard; Kitala, Philip (Dryad, 2017)
The impacts of vaccination on the transmission of Rift Valley fever virus
(RVFV) have not been evaluated. We have developed a RVFV transmission
model comprising two hosts -- cattle as a separate host and sheep and
goats as one combined host (herein after referred to as sheep) -- and two
vectors -- Aedes species (spp) and Culex spp -- and used it to predict the
impacts of: (1) reactive vaccination implemented at various levels of
coverage at pre-determined time points, (2) targeted vaccination involving
either of the two host species, and (3) a periodic vaccination implemented
biannually or annually before an outbreak. Methodology/Principal Findings:
The model comprises coupled vector and host modules where the dynamics of
vectors and hosts are described using a system of difference equations.
Vector populations are structured into egg, larva, pupa and adult stages
and the latter stage is further categorized into three infection
categories: susceptible, exposed and infectious mosquitoes. The survival
rates of the immature stages (egg, larva and pupa) are dependent on
rainfall densities extracted from the Tropical Rainfall Measuring Mission
(TRMM) for a Rift Valley fever (RVF) endemic site in Kenya over a period
of 1827 days. The host populations are structured into four age classes
comprising young, weaners, yearlings and adults and four infection
categories including susceptible, exposed, infectious, and immune
categories. The model reproduces the 2006/2007 RVF outbreak reported in
empirical surveys in the target area and other seasonal transmission
events that are perceived to occur during the wet seasons. Mass reactive
vaccination strategies greatly reduce the potential for a major outbreak.
The results also suggest that the effectiveness of vaccination can be
enhanced by increasing the vaccination coverage, targeting vaccination on
cattle given that this species plays a major role in the transmission of
the virus, and using both periodic and reactive vaccination strategies.
Conclusion/Significance: Reactive vaccination can be effective in
mitigating the impacts of RVF outbreaks but practically, it is not always
possible to have this measure implemented satisfactorily due to the rapid
onset and evolution of RVF epidemics. This analysis demonstrates that both
periodic and reactive vaccination ought to be used strategically to
effectively control the disease.
Gachohi et al RVF Model codeThis code, implemented in R, is about
simulating population dynamics of two species of mosquitoes namely Aedes
and Culex and two livestock species namely cattle and sheep. Hosts are
classified into four age groups (young, weaner, yearling and adult groups)
while vectors are classified into eggs, larvae, pupae and adults.
Transition rates govern the population dynamics. Further, the code
simulates transmission dynamics of Rift Valley fever virus between the
mosquitoes and the livestock. Mosquito growth is regulated by amounts of
rainfall implicitly through probability functions - suitability function
for Aedes and logistic distribution function for Culex. The code is used
to simulate diverse policy-relevant interventions on the effectiveness of
reactive and periodic Rift Valley fever vaccination strategies.Modelling
vaccination strategies against Rift Valley fever in livestock in Kenya:
Precipitation dataThis data contains precipitation data used to drive
mosquito population growth. In the code, the rain is sourced as follows:
Rain<-read.csv("D:\\RVF R model rain\\Rain.csv",
header=TRUE) saved in D in a folder RVF R model rain under fie name
Rain.csv. To import precipitation data, download the data from Dryad and
save in your PC and import appropriately to run the model.Rain.csv
Keywords: Rift Valley fever; simulation model